Clinical Outcome Of Tolosa-Hunt Syndrome After Intravenous Steroid Therapy: A Case Report - Bintang, Andi K.; Umbas, Juliet CG.; Basri, Muhammad I.; Tammasse, Jumraini (Hasanuddin University, 2021)
Objectives: Tolosa-Hunt syndrome (THS) is caused by an idiopathic inflammatory process in the cavernous sinus, superior orbital fissure, or orbit. THS is a rare disease. The main clinical symptoms are ophthalmoplegic pain, accompanied by ipsilateral headache, paresis of one or more ipsilateral III, IV, and or VI cranial nerves, MRI or biopsy abnormalities, and cannot be categorized as other diseases. THS resolves adequately with corticosteroids within 24-72 hours of therapy.Methods: Male, 53 years old, was admitted for painful right ophthalmoplegia, constant onset, two weeks, ipsilateral headache, accompanied by diplopia and right eyelid ptosis.Â There was no history of fever, trauma, or similar illness. Neurological examination showed exotropia due to paresis of the right III and IV cranial nerves. Analgesics can not relieve the pain. Laboratory findings, CT angiography, and brain MRI were normal.Result: There was clinical improvement within 24 hours after initiation of methylprednisolone followed by tapering-off oral prednisone.Conclusion: THS is a diagnosis of exclusion and must be distinguished from other causes of painful ophthalmoplegia. Careful follow-up is required to diagnose THS. The diagnosis should not depend on MRI alone but should be adjusted according to clinical findings and therapeutic response.